The fight for equality in east Africa: An analysis of sexual gender-based violence in Central African Republic, democratic republic of Congo and Uganda - Akina Mama wa Afrika (Akina Mama wa Afrika, 2018)
This policy brief will contain a summarized analysis on how effective the implementation of the Kampala Declaration on SGBV, the Goma Declaration on eradicating Sexual Violence and Ending Impunity in the Great Lakes, and UN Resolution 1325 have been in Central African Republic, Democratic Republic of Congo, and Uganda. These three policy frameworks are key for completely eradicating sexual gender-based violence and should be the basis for the continued fight for gender equity in Sub-Saharan Africa.